2011
DOI: 10.1128/cmr.00059-10
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Tuberculosis in Resource-Poor Countries: Challenges and Opportunities

Abstract: SUMMARY With an estimated 9.4 million new cases globally, tuberculosis (TB) continues to be a major public health concern. Eighty percent of all cases worldwide occur in 22 high-burden, mainly resource-poor settings. This devastating impact of tuberculosis on vulnerable populations is also driven by its deadly synergy with HIV. Therefore, building capacity and enhancing universal access to rapid and accurate laboratory diagnostics are necessary to control TB and HIV-TB coinfections in resource-limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
415
2
14

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(459 citation statements)
references
References 164 publications
11
415
2
14
Order By: Relevance
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 82%
“…Culture was performed using solid (Lowenstein-Jensen) and liquid (MGIT BACTEC 960) media using standard methodologies [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…Бројне студије су показале високу осјетљивост код препарат-позитивних респираторних (90-100%), те нижу код препарат-негативних респираторних (50-95.9%) и нереспираторних узорака (23.53-98%). За респираторне узорке, укупна осјетљивост теста варира од 83% до 100%, а укупна специфичност од 91.3% до 100% (Parsons et al, 2011;Tortoli et al, 2012). PPV COBAS AMPLICOR MTB Теста варира од 61.2% до 100%, док је негативна предиктивна вриједност (NPV) од 33.3% до 98.4%, у овисности од врсте респираторних узорака (Fegou et al, 2005).…”
Section: сажетакunclassified
“…COBAS AMPLICOR MTB Тест је показао нижу осјетљивост код препарат-негативних узорака која је у овом истраживању износила 83.33%. На основу резултата досадашњих студија примјена COBAS AMPLICOR MTB Теста код препарат-негативних узорака спутума је показала осјетљивост од 50% до 95.9% (Parsons et al, 2011). Rajalahti et al наводе да осјетљивост теста код препарат-негативних узорака може бити знатно повећана ако се анализе раде на три узастопна узорка спутума (Rajalahti et al).…”
Section: дискусијаunclassified
“…There are a variety of methods were used such as clinical findings, X-ray chest, Microscopy-AFB, Tuberculin sensitivity test (PPD), microbiological culture method, PCR and Histopathology [5]. The standard TB diagnostic method in developing countries continues to be the sputum smear microscopy [6]. It was developed in 1880 and has remained almost the identical given that it relies on the presence of acid-fast bacilli (AFB) in the stained smear [7].…”
Section: Introductionmentioning
confidence: 99%